Online Learning on Children's Language Development During the COVID-19 Pandemic - Wisnu Kristanto; Alfina Citrasukmawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The period of the COVID-19 pandemic impacted education, especially on early childhood education aged 5-6 years. This study aims to determine the effect of online learning on developing language aspects of children aged 5-6 years. The method used is True Experimental Design by comparing face-to-face learning at school and online education at home. The research subjects consisted of two groups, namely experimental and control, with 40 PAUD children from Kindergarten Schools in Surabaya and Gresik. Based on the Asymp.Sig value shows that online learning significantly affects early childhood language development during the Covid-19 pandemic. The reason is, face-to-face learning cannot be done optimally, with reduced learning hours during the Covid-19 pandemic. Conversely, online learning can be done anywhere and anytime, even though the place and distance are different. 0.000 0.05. Online learning that is carried out has the advantage of not having space and time boundaries so that the need for increasing children's speaking, reading, and writing skills can be met.